Challenges in transitioning to low carbon living for lower income households in Australia. Issue 1 (2nd January 2019) - Liu, Edgar; Judd, Bruce; Santamouris, Mattheos
ABSTRACT: In the move towards low carbon living, the challenges faced by lower income groups are often overlooked. Recent rises in electricity costs disproportionate to income make this a more critical issue. Based on findings from focus group discussions with 164 lower income households and 18 stakeholders across 4 different climate zones in Australia, this paper reveals the barriers that lower income households face in improving their residential energy efficiency and in achieving low carbon living. While limited financial capacity is generally understood as a significant barrier preventing lower income households from taking up technologies to achieve greater energy efficiency and transition to low carbon living, our findings show that a mix of financial and non-financial barriers exist. These include their ability to afford energy efficient household products, control over thermal comfort and energy efficiency levels of their homes, and lack of access to reliable information. These barriers are revealed to have significant impacts on the household finances, health, and social well-being of these lower income households. The concluding discussion puts forward policy suggestions on how some current assistance and incentive programmes encouraging low carbon living could be adjusted to ensure more equitable access, encourage uptake, and improve low carbon outcomes.